Alcoholic liver disease confers a worse prognosis than HCV infection and non-alcoholic fatty liver disease among patients with cirrhosis: An observational study - Marot, Astrid (PLoS One, 2017)
BACKGROUND: Cirrhosis is a heterogeneous clinical condition that includes patients at wide-ranging stages of severity. The role of the underlying liver disease on patient prognosis remains unclear. AIM: To assess the impact of the underlying liver disease on the occurrence of hepatocellular carcinoma (HCC) and death. METHODS: Data related to the occurrence of HCC and death were collected during a 21-year period among patients with cirrhosis related to alcoholic liver disease (ALD) (n = 529), chronic hepatitis C virus (HCV) infection (n = 145) or non-alcoholic fatty liver disease (NAFLD) (n = 78). RESULTS: At inclusion, ALD patients were younger than HCV and NAFLD patients (56 vs. 67 vs. 63 years; p<0.001) and had worse liver function (percent of patients with Child-Pugh stages B or C: 48% vs. 8% vs. 17%; p<0.001). During follow-up, 85 patients developed HCC and 379 died. The 10-year cumulative incidence rate of HCC was lower in ALD patients than in HCV and NAFLD patients (8.4% vs. 22.0% vs. 23.7%; p<0.001). The 10-year cumulative incidence rates of mortality were not statistically different between ALD, HCV and NAFLD patients (58.1% vs. 47.7% vs. 49.9%; p = 0.078). Alcohol abstinence and viral eradication were associated with reduced mortality among ALD and HCV patients, respectively. In multivariate analyses, ALD was associated with a reduced risk of HCC (0.39; 95% CI, 0.20–0.76; p = 0.005) but with a higher risk of mortality (1.53; 95% CI, 1.20–1.95; p<0.001). ALD patients died more frequently from decompensation of cirrhosis. CONCLUSION: Despite a lower incidence of HCC, patients with ALD-related cirrhosis have a worse outcome than those with chronic HCV infection or NAFLD-related cirrhosis.